Rubimaillin decreases the viability of human ovarian cancer cells via mitochondria-dependent apoptosis - Siwei, Zhang; Zhen, Wu; Zhi, Zhou; Xuguang, Hu; Yousheng, Li (Cellular and Molecular Biology, 2019)
This study was aimed to investigate the anti-tumor activity of rubimaillin in vitro, and the mechanism involved. The inhibitory effect of rubimaillin on cell proliferation was determined with MTT assay. Apoptosis was assayed using AV/PI double staining, while the mitochondrial membrane potential of SKOV-3 cells was determined with Rhodamine 123 (Rh123) staining. Western blot assay was used to determine the effect of rubimaillin on the expressions of Bcl-2, Bax, PARP, cleaved PARP, caspase3, cleaved caspase3, and other apoptosis-related proteins in SKOV-3 cells. Rubimaillin inhibited the growth of SKOV-3 cells in a concentration-dependent manner and induced apoptosis of tumor cells through the mitochondrial apoptosis pathway. These results indicate that rubimaillin is a potential anti-ovarian cancer drug.